EVOLUTION AND GLOBAL DISTRIBUTION OF GENETICALLY MODIFIED SOYBEAN AREA IN THE PERIOD 2014-2018 - Dorina BONEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Currently, genetically modified (GM) crops are an important part of world agriculture, offering numerous benefits to farmers. This study investigates the dynamics of the cultivated area with GM crops, especially with genetically modified (GM) soybean, for the period 2014–2018, by country and by transgenic trait, using ISAAA and FAOSTAT databases. In the studied period, the top 5 GM crops countries were USA, Brazil, Argentina, Canada and India which totalled 166.1 million hectares or 89.5% of the global area. Regarding GM soybean, the top 5 countries were USA, Brazil, Argentina, Paraguay and Canada which cultivated 89.9 million hectares or 96.8% of the global area with this crop. The linear regression and the Pearson correlation coefficient have pointed out a general increasing trend for both cultivated areas. The USA and Brazil occupied the leading position in world with 32.93 and 32.55 million hectares of GM soybean, respectively. Herbicide tolerance (HT) has been consistently the dominant transgenic trait for GM soybean in USA, Argentina, Paraguay and Canada. In Brazil, the cultivated areas with stacked HT/IR traits have been larger than the areas cultivated with a single HT trait, in the last 3 years. As a conclusion, the global area of GM soybean will continue to increase due to its important economic role in the agriculture development and environmental benefits.